Limited Effects of Type I Interferons on Kyasanur Forest Disease Virus in Cell Culture. - Bradley W M Cook; Charlene Ranadheera; Aidan M Nikiforuk; Todd A Cutts; Darwyn Kobasa; Deborah A Court; Steven S Theriault (Public Library of Science (PLoS), 2016)
BACKGROUND:The tick-borne flavivirus, Kyasanur Forest disease virus (KFDV) causes seasonal infections and periodic outbreaks in south-west India. The current vaccine offers poor protection with reported issues of coverage and immunogenicity. Since there are no approved prophylactic therapeutics for KFDV, type I IFN-α/β subtypes were assessed for antiviral potency against KFDV in cell culture. METHODOLOGY/PRINCIPAL FINDINGS:The continued passage of KFDV-infected cells with re-administered IFN-α2a treatment did not eliminate KFDV and had little effect on infectious particle production whereas the IFN-sensitive, green fluorescent protein-expressing vesicular stomatitis virus (VSV-GFP) infection was controlled. Further evaluation of the other IFN-α/β subtypes versus KFDV infection indicated that single treatments of either IFN-αWA and IFN-αΚ appeared to be more effective than IFN-α2a at reducing KFDV titres. Concentration-dependent analysis of these IFN-α/β subtypes revealed that regardless of subtype, low concentrations of IFN were able to limit cytopathic effects (CPE), while significantly higher concentrations were needed for inhibition of virion release. Furthermore, expression of the KFDV NS5 in cell culture before IFN addition enabled VSV-GFP to overcome the effects of IFN-α/β signalling, producing a robust infection. CONCLUSIONS/SIGNIFICANCE:Treatment of cell culture with IFN does not appear to be suitable for KFDV eradication and the assay used for such studies should be carefully considered. Further, it appears that the NS5 protein is sufficient to permit KFDV to bypass the antiviral properties of IFN. We suggest that other prophylactic therapeutics should be evaluated in place of IFN for treatment of individuals with KFDV disease.